Metabolic syndrome, left ventricular hypertrophy and carotid atherosclerosis in hypertension: A gender-based study. (June 2013) - Cuspidi, Cesare; Sala, Carla; Lonati, Laura; Negri, Francesca; Rescaldani, Marta; Re, Annalisa; Meani, Stefano; Mancia, Giuseppe
Abstract Background. The influence of gender on the association between metabolic syndrome (MS) and subclinical organ damage (OD) has been poorly investigated. The aim of this study was to investigate whether the risk of developing left ventricular hypertrophy (LVH) and carotid atherosclerosis is different in men and women with MS. Methods. A total of 3752 untreated and treated hypertensive patients (mean age 53.3 ± 12.6, 52.7% men) were considered for this analysis. All patients underwent standard ultrasonographic investigations searching for LVH and carotid atherosclerosis. The MS was defined according to ATP III criteria. Results. LVH was more prevalent in women and men with the MS compared with their counterparts (58% vs 34% and 48% vs 33%, respectively, p < 0.001). This was also the case for carotid plaque prevalence (61% vs 42% and 57% vs 44%, p < 0.001). The prevalence of OD was not different between men and women with MS, after adjusting for confounders. In multivariate analysis, abdominal obesity was the most important MS component independently related to LVH in both genders, followed by blood pressure. As for carotid plaques, blood pressure, hyperglycemia and hypertriglyceridemia turned out to be independent correlates regardless of gender. Conclusions. Our data indicate that MS is associated with a higher risk of LVH and carotid atherosclerosis irrespective of gender; these findings do not support a gender influence in the association between MS and subclinical OD.